2004
DOI: 10.2320/matertrans.45.2878
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Discharge Surface Alloying of Superalloy Haynes 230 with Aluminum and Molybdenum

Abstract: Surface alloying of superalloy Haynes 230 was performed using either Al-Mo mixture powders suspended in kerosene or Al-Mo composite electrode during the electrical discharge alloying (EDA). For suspending Al-Mo powders in kerosene, the Cr 23 C 6 , WC 1Àx , and graphite phases exist in the alloyed layer of the EDA specimen with negative electrode polarity, while the specimen with positive electrode polarity exhibits no alloying phase except the raw material phase. For employing the Al-Mo electrode with negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Conversely, the oxidation resistance of the other EDA specimen alloyed with negative electrode polarity was even worse than that of the unalloyed superalloy. In their previous work Bai et al [16] presented the EDA process of the superalloy Haynes 230 with aluminum and molybdenum, and the alloying effects of different EDA conditions have also been determined and compared. Suitable experiment conditions can help to form an aluminum-rich layer on the surface of the superalloy.…”
Section: Research Work On Machining Of Inconelmentioning
confidence: 99%
“…Conversely, the oxidation resistance of the other EDA specimen alloyed with negative electrode polarity was even worse than that of the unalloyed superalloy. In their previous work Bai et al [16] presented the EDA process of the superalloy Haynes 230 with aluminum and molybdenum, and the alloying effects of different EDA conditions have also been determined and compared. Suitable experiment conditions can help to form an aluminum-rich layer on the surface of the superalloy.…”
Section: Research Work On Machining Of Inconelmentioning
confidence: 99%
“…It was demonstrated that inter-granular oxidation and internal oxidation occurred at 982°C and 1093°C after 300 h exposure, respectively. Further, many researcher tried to improve the oxidation behavior of Haynes 230 by several methods, using alloying [22,23], electrical discharge alloying (EDA) [24,25], MOCVD [26] or various surface modification [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Average recast thickness is <11 m. Several trim passes show no significant change in workpiece microhardness variation with cracking confined to the recast layer. Bai et al (2004) develop electrical discharge surface alloying of superalloy Haynes 230 with Al and Mo. The produced specimen using the Al-Mo electrode with positive polarity shows an alloyed layer constituted mainly with NiAl phase.…”
Section: Introductionmentioning
confidence: 99%